Bacterial community structure of Physalis peruviana L. fruit exocarp and the presence of pathogens with possible implications on food safety - Tenea, Gabriela N.; Molina, Diana (Frontiers in Plant Science, 2024)
Cape gooseberry (Physalis peruviana L.) is a well-consumed crop in Ecuador, whose fruits are abundant in bioactive molecules. Its rapid post-harvest deterioration and safety limit its market potential. To gather baseline data on the prevalence of bacterial taxa among groups, we employed 16S ribosomal RNA (16S rRNA) amplicon gene sequencing to detect changes in the bacterial community structure in cape gooseberry fruits harvested from an organic farm production system (# 270 samples x two ripeness stages), and fruits obtained from an open-air market (# 270). This is the first report of bacterial taxa inhabiting cape gooseberry fruits. Shannon's diversity index revealed that the fruits purchased from the market and the unripe stage had the highest level of bacterial diversity (average Shannon indices of 3.3 and 3.1) followed by those collected from the field at the mature ripe stage (2.07). Alpha diversity analysis indicated that there were no significant differences in the number of taxa or evenness within the sample, whereas there was a significant difference in beta diversity between the groups. Rhizobiaceae was the most abundant family in fruits originating from the field regardless of the ripe stage, while Acetobacteraceae, Pseudomonadaceae, Fusobacteriaceae, Bacteroidaceae, and Erwiniaceae were the most abundant families in the market group. At the genus level, Liberibacter was the most abundant phytopathogen in fruits originating from the field, while Gluconobacter was the most abundant in samples collected from the market. The phytopathogen Candidatus_Liberibacter was the most abundant in samples collected from the field, while the fruits purchased from the market stands contained opportunistic enteric pathogens such as Escherichia vulneris, Klebsiella pneumoniae, and K. variicola, their relative abundance varied with the sample. In addition, potential pathogens of animal origin such as Fusobacterium necrophorum, Porphyromonas levii, Helcococcus ovis, and Trueperella pyogenes were found in almost all samples at varying relative abundance. Our study provides basic information on the microbiome of cape gooseberries from agriculture fields to the table along with the detection of several pathogenic microorganisms with possible impact on food safety and public health therefore, strategies for reducing bacterial contamination in both farm and retail markets are compulsory.